Design and Implementation of a Novel IoT Carbon Monoxide Detection System Using IP-based WiFi Location - Zerrouki, Hadj; Hadjila, Mourad; Azzaz-Rahmani, Salima (Journal of Informatics and Mathematical Sciences, 2021)
Throughout the world and more particularly in Algeria, Carbon Monoxide (CO) poisoning is one of leading cause of death and taking worrying proportions. Colorless, odorless, non-irritating, this silent killer is responsible for more than 100 deaths each year, for several thousand hospitalizations, especially during the winter period when the cold sets in and the demand for heating homes increases. However, the protection of human lives becomes a top priority and consequently the CO leak location will have to be done as quickly as possible to provide first aid in record time. In this paper we present the design, development and a case of use of a novel Internet-of-Things (IoT) carbon monoxide detection system using IP-based WiFi location. Once the CO leak occurs, a notification alert message is sent to civil defense containing the detected CO amount and the public IP address used to extract the real location address of the CO leak by sending a request to a database provided by an internet service provider and therefore provide the necessary assistance in a timely manner by contacting the nearest unit.